Les intellectuels français au service de la propagande franquiste pendant la guerre civile : le cas de la revue Occident (1937-1939) - Darío Varela Fernández (Cahiers de Civilisation Espagnole Contemporaine)
The Spanish Civil War aroused strong passions in France between partisans and detractors of the Republic. The international propaganda of the uprisings against the republican regime has been studied but, until now, research have been confined to analyzing primarily the role played by the Spaniards. This work aims to analyze the French intellectuals who, through their commitments and their works, contributed to glorifying the Francoist cause. The motivations of the various French actors prove that the Spanish Civil War was not only in Iberian territory but a field of international cultural warfare for the reactionary forces of the 1930s.